2009
DOI: 10.1111/j.1365-2044.2009.06079.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency jet ventilation through a supraglottic airway device: a case series of patients undergoing extra‐corporeal shock wave lithotripsy

Abstract: SummaryHigh frequency jet ventilation has been shown to be beneficial during extra‐corporeal shock wave lithotripsy as it reduces urinary calculus movement which increases lithotripsy efficiency with better utilisation of shockwave energy and less patient exposure to tissue trauma. In all reports, sub‐glottic high frequency jet ventilation was delivered through a tracheal tube or a jet catheter requiring paralysis and direct laryngoscopy. In this study, a simple method using supraglottic jet ventilation throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As expected, HFJV-assisted cases demonstrated significantly lower diaphragmatic excursion compared to IPPV (mean 1.3 mm, compared with 20 mm for IPPV), and similar results (1.3 mm excursion with HFJV assistance compared with 11 mm for IPPV) were observed intraprocedurally in the five cases with HFJV assistance, although did not reach statistical significance likely due to small sample size. These measurements are comparable with reported excursion of 1–3 cm during quiet breathing and conventional IPPV [29, 30] and with prior studies reporting reduced diaphragmatic motion during HFJV-assisted extracorporeal shockwave lithotripsy [25].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected, HFJV-assisted cases demonstrated significantly lower diaphragmatic excursion compared to IPPV (mean 1.3 mm, compared with 20 mm for IPPV), and similar results (1.3 mm excursion with HFJV assistance compared with 11 mm for IPPV) were observed intraprocedurally in the five cases with HFJV assistance, although did not reach statistical significance likely due to small sample size. These measurements are comparable with reported excursion of 1–3 cm during quiet breathing and conventional IPPV [29, 30] and with prior studies reporting reduced diaphragmatic motion during HFJV-assisted extracorporeal shockwave lithotripsy [25].…”
Section: Discussionsupporting
confidence: 89%
“…The HFJV is a mechanical ventilation method initially described in 1977 by Klain and Smith [28], in which small tidal volumes of pressurised gas are delivered through a narrow-bore endotracheal catheter at very high respiratory rates. The technique facilitates adequate gas exchange while minimising diaphragmatic excursion, and thoracoabdominal target lesions normally subject to significant respiratory positional variation are rendered relatively motionless [14, 15, 25]. Several recent interventional radiology reports have demonstrated improved lesion targeting, reduced technical difficulty and procedural time, and reduced patient radiation dose during thermal ablation of lung, liver, and renal tumours [1924].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 We observed an increase in Etco 2 for some patients but do not routinely measure arterial blood gases. Supraglottic airways can be electively used to deliver HFJV 14 although we do so infrequently. We include 1 case but the provider reported low satisfaction due to needing repeated adjustment of driving pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of percutaneous ablation, the only series we found in literature was a retrospective observational study published in 2011 in which nine patients with hepatic or renal lesions were treated under HFJV [4]. We have also acknowledged several reports associating high frequency jet ventilation with extracorporeal shock wave lithotripsy [5][6][7], a technique similar to some extent to HIFU. It was shown that HFJV reduced urinary stone movement, which increased lithotripsy efficiency with better utilization of shockwave energy and less patient exposure to tissue trauma.…”
Section: Dear Editormentioning
confidence: 99%